The Use of Datasets for Theoretical Subjects to Validate Vitamin A–Related Methods and Experimental Designs - Green, Michael H; Green, Joanne Balmer (The Journal of nutrition, 2022)
We review recent work in which model-based compartmental analysis has been applied to data for theoretical human subjects in order to study questions related to vitamin A kinetics and metabolism. Using model simulations in this way, one can validate experimental designs, evaluate or improve vitamin A assessment methods, study the influence of perturbations on assessment methods, and/or advance information related to retinol kinetics. We also provide some information on the rationale for assigning physiologically appropriate values for specified characteristics [e.g., plasma retinol concentration, vitamin A total body stores (TBS), vitamin A intake] to hypothetical individuals, and in addition, we outline how one might first select an appropriate compartmental model for whole-body vitamin A metabolism and then specify physiologically reasonable values for the associated retinol kinetic parameters. In the studies discussed here, the Simulation, Analysis, and Modeling software was used to simulate responses in key model compartments for hypothetical subjects so that model predictions could be compared to assigned values or projected outcomes. For example, in the case of the retinol isotope dilution (RID) method that is used to assess vitamin A status, application of this approach has provided a way to evaluate the accuracy of TBS predictions under different steady state and non-steady state conditions, thus increasing confidence about the validity of RID results obtained in the field. Although datasets for theoretical subjects have been used to evaluate protocols in pharmacokinetics, to our knowledge, other nutrition researchers have not previously used approaches such as those described here. Our results to date indicate that this strategy has the potential to provide useful information related not only to vitamin A but perhaps to other nutrients as well.